Restorative Approach Resolution Mecanism For Victims of Crimes Committed by Children - Yedi Kusnadi; Syahird, Ahmad; Fatihani Baso (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This thesis research aims to analyze the compensation mechanism in the SPPA Law through a restorative justice approach in the Juvenile Criminal Justice System, as well as to analyze the application of compensation in restorative justice in the Juvenile Criminal Justice System. This research is normative empirical research in conducting research, the author conducts field research by choosing the research location of Pinrang Police, Pinrang District Attorney. The results showed that 1) Restorative justice or justice or deliberation-based justice is a process of Diversion, where all parties involved in a criminal offense must jointly overcome problems and create an obligation to make things better by involving victims, children, and the community in finding a solution to repair, reconciliation, and reassurance that is not based on retaliation. The criminal justice process carried out by law enforcement officials if the child offender is proven guilty, ideally and should be sentenced to return to parents. Efforts to implement the law's order that imprisonment of children is the last resort (ultimum remedium) should also be in line with the understanding that the best decision is the action to return the child offender to his parents to be educated and fostered properly. 2) The application of restitution through restorative justice in the Juvenile Justice System is determined by the agreement of the parties to achieve peace. After compensation is paid, the criminal case committed by the child is truly declared over, as evidenced by a certificate signed by the parties. In the process of deliberation or mediation on behalf of witnesses or relatives, but in its implementation there are often obstacles due to law enforcement factors and community factors. For this reason, it is necessary to have specific legal arrangements in the legislation regarding the amount of compensation that is the obligation of children as perpetrators of criminal acts against victims by adjusting the hierarchy of punishment imposed in order to ensure legal certainty.